Perspectives and experiences regarding pre-exposure prophylaxis (PrEP) in a community sample of Veterans with unhealthy alcohol use: overall and across sexual orientation and gender identity - Olivia V. Fletcher; Kristine Beaver; Elizabeth J. Austin; Jenna van Draanen; E. Jennifer Edelman; Emily C. Williams (Addiction Science & Clinical Practice)
Abstract Background Unhealthy alcohol use is an independent, modifiable risk factor for HIV, but limited research addresses alcohol use and HIV prevention synergistically. Groups that experience chronic stigma, discrimination, and/or other marginalization, such as sexual and gender minoritized groups, may have enhanced HIV risk related to unhealthy alcohol use. We described awareness of and experiences with pre-exposure prophylaxis (PrEP) among a community sample of Veterans reporting unhealthy alcohol use (relative to those without), overall and across self-reported sexual orientation and gender identity. Methods Using data collected from a national online survey of Veterans recruited via Facebook ads, community organizations, and listservs, we assessed variation in four PrEP outcomes (knowledge, experience, willingness, and conversations with doctors) across patterns of unhealthy alcohol use among all respondents reporting any lifetime drinking (n = 1,041) and then within sexual orientation and gender identity groups using Chi-square or Fisher’s exact tests. Results Among 1,041 eligible Veterans, 440 (42%) screened positive for unhealthy alcohol use. Veterans with unhealthy alcohol use were not more likely to have heard of PrEP (58.2% vs. 55.4%, p = 0.37), but trended toward more likely to have taken PrEP (7.5% vs. 5.0%, p = 0.09), to be willing to take PrEP (30.5% vs. 27.6%, p = 0.06), and to have spoken with a doctor about PrEP (11.4% vs. 7.7%, p = 0.04). Those with heavy episodic drinking also trended toward higher prevalence of PrEP awareness (60.0% vs. 54.6%, p = 0.09), and were more likely to have taken PrEP (8.3% vs. 4.7%, p = 0.02), to be willing to use PrEP (34.6% vs. 25.5%, p < 0.01), and to have had conversations with doctors about PrEP (12.7% vs. 7.2%, p < 0.01). Similar patterns were observed for severe unhealthy alcohol use and past-year frequent heavy episodic drinking. Generally, sexual/gender minoritized Veterans with unhealthy alcohol use reported more PrEP-affirming responses than those without but associations with unhealthy alcohol use were similar. Conclusions Unhealthy alcohol use was prevalent, particularly among Veterans with minoritized sexual orientation/gender identity, but not clearly linked to increased PrEP-literacy and use despite its known status as an HIV risk factor. Across groups, > 25% of individuals were willing to take PrEP. Interventions targeting both alcohol use and HIV prevention should capitalize on this.